1968
DOI: 10.1111/j.1540-6261.1968.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mergers and Acquisitions on the Market Value of Common Stock*

Abstract: THIS STUDY EXAMINES the relation between stock-price changes and the consummation of mergers and acquisitions. Although mergers have been analyzed in depth for possible economic benefits, very little research has centered on accompanying effects on equity values.From a list of business combinations involving New York Stock Exchange firms during the years 1961 through 1965, thirty-five mergers are randomly selected for analysis. In all mergers eligible for selection, the acquired company is at least ten per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Time 0 was operationally defined as a minimum of two months before the first public announcement of the merger n order to exclude possible anticipation effects in the price. Past merger studies [especially [1], [5] and [7] as well as investigations by the author indicated that this measurement period was reasonable.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Time 0 was operationally defined as a minimum of two months before the first public announcement of the merger n order to exclude possible anticipation effects in the price. Past merger studies [especially [1], [5] and [7] as well as investigations by the author indicated that this measurement period was reasonable.…”
mentioning
confidence: 69%
“…A review of the merger literature including studies by Hogarty [5], Reid [12], Weston and Mansinghka [14], Block [1] and Kelly [7] yields the general conclusion that mergers do not increase the returns to shareholders. Examination of these findings in light of equation (1) produces several reasons for questioning them, however.…”
Section: A Measure Of Merger Returns and Its Relationship To Pastmentioning
confidence: 99%
“…In addition, a larger number of Vietnamese M&A transactions in the 2005-2010 period as reported by Vuong et al (2010), as well as the increasing trend in 2011-12, suggest that banks' motivation to acquire capital assets and brand values in the local market, while empirical evidence appears to have indicated that immediate profits are not always the expectations from acquiring firms (e.g., Block, 1968;Shick, 1972;Focarelli et al, 2002, Pop, 2006. In this sense "business concentration" can be regarded as the "keyword" although Ijiri and Simon (1971) reported empirical results rejecting the hypothesis that M&A is a profound way to reduce competition through increasing domination of M&A players.…”
Section: Literature On Post-manda Performance and Why Creative Performamentioning
confidence: 87%